1988
DOI: 10.1007/bf00314352
|View full text |Cite
|
Sign up to set email alerts
|

Persistent intrathecal secretion of oligoclonal, Borrelia burgdorferi-specific IgG in chronic meningoradiculomyelitis

Abstract: In the cerebrospinal fluid IgG of five patients with lymphomeningoradiculitis (Bannwarth's syndrome) and radiculomyelitis studied by immunoblot technique an oligoclonal pattern was found. Most of these oligoclonal bands were specific for Borrelia burgdorferi. In patients suffering from chronic meningoradiculomyelitis, repeated CSF examination by this technique showed persistent secretion of identical IgG bands. Thus, the specific humoral immune response and the disease activity could be documented over the cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0
2

Year Published

1988
1988
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 25 publications
2
15
0
2
Order By: Relevance
“…No cross-reactivity of RA77 with T. pallidum spirochetes or E. coli could be detected, indicating that RA77 is specific for B. burgdorferi. This finding of a B. burgdorferi-specific antibody produced by a cePC is consistent with previous studies showing that OCB in the CSF of NB patients contain antibodies directed against B. burgdorferi (10,15), particularly in view of recent data from our laboratory supporting the conclusion that cePC are in fact the producers of OCB (unpublished data). To date, the only other inflammatory disease for which a link between CNS-derived plasma cells and the causative agent has been demonstrated is subacute sclerosing panencephalitis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…No cross-reactivity of RA77 with T. pallidum spirochetes or E. coli could be detected, indicating that RA77 is specific for B. burgdorferi. This finding of a B. burgdorferi-specific antibody produced by a cePC is consistent with previous studies showing that OCB in the CSF of NB patients contain antibodies directed against B. burgdorferi (10,15), particularly in view of recent data from our laboratory supporting the conclusion that cePC are in fact the producers of OCB (unpublished data). To date, the only other inflammatory disease for which a link between CNS-derived plasma cells and the causative agent has been demonstrated is subacute sclerosing panencephalitis.…”
Section: Discussionsupporting
confidence: 92%
“…Analysis of immunoglobulins (Ig) in the CSF has revealed specificity for B. burgdorferi (10,15) and also for CNS autoantigens (12). However, the mechanisms underlying B. burgdorferi-directed humoral immune defense and CNS tissue damage still remain poorly understood, and more in-depth characterization of the focused antibody response in the CSF has been hampered by both the limited availability and the oligoclonal/polyclonal composition of CSF Ig.…”
mentioning
confidence: 99%
“…This strategy revealed full-length cDNA sequences of matching Ig chains and allowed us to produce recombinant OCB (rOCB) antibodies. As proof of concept, we show that an OCB antibody from a patient with neuroborreliosis (NB) binds to a protein from Borrelia (25). Then, we characterized six rOCB antibodies from four MS patients and identified three different OCB target autoantigens.…”
Section: Significancementioning
confidence: 97%
“…Studies in which the specificity of CSF OGBs was analyzed showed that the antibodies were directed against the agent that causes disease (1)(2)(3)(4)(5)(6)(7)(8). For example, the OGBs in SSPE CSF and brain are antibodies directed against MV (1).…”
mentioning
confidence: 99%